2011
DOI: 10.1103/physreve.83.056301
|View full text |Cite
|
Sign up to set email alerts
|

Separation of deformable particles in deterministic lateral displacement devices

Abstract: Using numerical simulations, we study the separation of deformable bodies, such as capsules, vesicles, and cells, in deterministic lateral displacement devices, also known as bump arrays. These arrays comprise regular rows of obstacles such as micropillars whose arrangements are shifted between adjacent rows by a fixed amount. We show that, in addition to the zigzag and laterally displaced trajectories that have been observed experimentally, there exists a third type of trajectory which we call dispersive, cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 15 publications
4
49
0
Order By: Relevance
“…the case of G s = 0.01 in figure 5c). As mentioned in the introduction, Beech et al (2012) observed that the blood cell was more prone to the zigzag model, as its deformability increased, whereas the numerical results of Quek et al (2011) showed the opposite tendency. This contradiction can now be resolved from our simulations, since the particle deformability of Beech et al (2012) was notably large whereas that of Quek et al (2011) was relatively small.…”
Section: Effects Of Particle Deformabilitymentioning
confidence: 91%
See 2 more Smart Citations
“…the case of G s = 0.01 in figure 5c). As mentioned in the introduction, Beech et al (2012) observed that the blood cell was more prone to the zigzag model, as its deformability increased, whereas the numerical results of Quek et al (2011) showed the opposite tendency. This contradiction can now be resolved from our simulations, since the particle deformability of Beech et al (2012) was notably large whereas that of Quek et al (2011) was relatively small.…”
Section: Effects Of Particle Deformabilitymentioning
confidence: 91%
“…Quek et al (2011) employed the immersed boundary method to investigate the effects of various control parameters on the separation of deformable particles in the DLD device, and observed that with the increase of particle deformability, the zigzag mode could be turned into the lateral-displacement mode, which is qualitatively opposite to the experimental observation of Beech et al (2012). Thus, further studies need to be carried out to understand the effects of particle deformability, which is the main aim of the present study.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Combining microfluidic systems with different readout techniques has produced powerful tools in the emerging area of the on-chip controlled handling and monitoring of biological and synthetic microparticles and nanoparticles, with especially great impact on biotechnology and environmental topics, such as hydrodynamic forces [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], optical methods [21,22], electric fields and dielectrophoresis [23][24][25][26][27] or acoustic fields , either isolated or combined with other fields.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] It has, in fact, been successfully used in a number of applications, especially for the separation of biological samples. [11][12][13][14][15][16][17][18] Although in most cases DLD is described (and investigated) as a size-based separation technique, it could also separate particles based on shape and flexibility 19,20 and may contribute to the growing field of chiral separation. 21,22 We have shown that a simple model 23,24 that describes the motion of a suspended sphere around an individual obstacle in the DLD array (which we refer to as a particle-obstacle collision) predicts the separation capability of the system.…”
Section: Introductionmentioning
confidence: 99%